Impact of Aerosols on the Convective Boundary Layer Development over Baghdad City - Abbood, Zainab M.; Al-Jiboori, Monim H.; Al-Taai, Osama T. (Iraqi Journal of Science, 2025)
The dynamics and physics of the atmospheric layer nearest to the Earth's surface are included in the boundary layer meteorology. This research aims to evaluate the impacts of aerosols at different altitudes with various optical properties on CBL development. The greatest impact occurs when aerosol absorption is low but close to the peak of CBL. The main objective of this research is to study the effect of aerosols which reduce the net heating, which in turn causes a decrease in the height of the CBL and increases the partitioning of the boundary layer. The methods used in the study depend on the hourly average height boundary taken from the European Centre for Weather Forecast (ECMWF) during the year 2021 over Baghdad City. It showed that the values of the height of the bounding layer during the winter were low, and they were high during the summer, while the values of the height of the bounding layer during the autumn were slightly higher than in the spring, and this was due to many reasons, such as astronomical and meteorological factors. The results showed that the values of the particulate matter PM1, 2.5, and10μg/m3 during the spring and autumn were high, while the values of the PM1, 2.5, and10 μg/m3 during the winter and summer were low, as well as PM10 μg/m3 were high, including a great boundary layer height and PM1, and 2.5 μg/ m3were low, including a slight boundary layer height. Also, PM10 μg/ m3 was high, including a great boundary layer height and PM1 and 2.5 were low including a slight boundary layer height, and this is due to many reasons, such as the optical depth of particle matter, solar heating, humidity, wind speed, precipitation, and humans’ activities.